Culturally diverse children and adolescents assessment, diagnosis, and treatment - Canino, Ian A.; Spurlock, Jeanne (Guilford, 1994)
Mental health professionals working with children are often faced with a number of obstacles from determining the situation specificity of the problem behavior to ascertaining the influence of the child's developmental level. When the clients are minority children, the clinical challenge is often compounded: Clinicians must move beyond the limitations of traditional assessment, diagnostic, and treatment approaches and learn how to determine the impact of cultural differences, poverty, discrimination, and acculturation issues. Addressing each of these elements, this important new volume shows mental health service providers how to work with economically disadvantaged children and adolescents from culturally diverse backgrounds. The book concentrates on the mental health needs of primarily those African-American, Latino, Asian-American, and American Indian children who are subject to numerous social stressors and whose families represent the lower socioeconomic levels